Pengaruh profitabilitas, leverage dan likuiditas terhadap financial distress - Hertina, Dede; Wahyuni , Linda Destya; Ramadhan , Galih Kharisma (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the effect of Profitability, Leverage and Liquidity on Financial Distress in the Property, Real Estate and Building Construction sectors listed on the Indonesia Stock Exchange in 2014-2018. The indicators tested in this study are Return on Asset (ROA), Debt to Asset Ratio (DAR), and Current Ratio (CR) as independent variables and Financial Distress (Springate S-score) as the dependent variable. The research method used is descriptive and verification methods. The population in this study were 45 companies in the Property, Real Estate and Building Construction sector listed on the Indonesia Stock Exchange in 2014-2018. The sampling technique based on purposive sampling obtained a sample of 16 companies for 5 years from 2014 to 2018 so that 80 observational data were obtained. The statistical analysis used in this study is the Panel Data regression analysis technique at the 5% significance level with the help of the EViews 9 application.The results show that partially the profitability ratio (ROA) and liquidity (CR) have a significant positive effect on Financial Distress which is proxied by theory. Springate S-score while the leverage ratio (DAR) has no effect on Financial Distress as proxied by the Springate S-score theory. Meanwhile, the ratio of profitability, leverage and liquidity simultaneously affects the Financial Distress of the Property, Real Estate and Building Construction sectors listed on the Indonesia Stock Exchange in 2014-2018.